Description of a new pygmy chameleon (Chamaeleonidae: Brookesia) from central Madagascar - Crottini, Angelica; Miralles, Aurélien; Glaw, Frank; Harris, D. James; Lima, Alexandra; Vences, Miguel (Zootaxa, 2012)
We describe a new Brookesia species from a forest fragment located 13 km south of Ambalavao in the southern part ofMadagascar’s central high plateau. Brookesia brunoi sp. nov. is one of the few arid-adapted Brookesia species inhabitingdeciduous forests on the western slope of the central high plateau of the island (around 950 m a.s.l.). So far the species hasonly been observed in the private Anja Reserve. The species belongs to the Brookesia decaryi group formed by arid-adapt-ed Brookesia species of western Madagascar: B. bonsi Ramanantsoa, B. perarmata (Angel), B. brygooi Raxworthy &Nussbaum and B. decaryi Angel. Brookesia brunoi differs from the other four species of the group by a genetic divergenceof more than 17.6% in the mitochondrial ND2 gene, and by a combination of morphological characters: (1) nine pairs oflaterovertebral pointed tubercles, (2) absence of enlarged pointed tubercles around the vent, (3) presence of poorly definedlaterovertebral tubercles along the entire tail, (4) by the configuration of its cephalic crest, and (5) hemipenial morphology.Based on our molecular phylogeny this species is sister to a clade containing B. brygooi, B. decaryi, and probably B. bonsifor which no ND2 sequences were available. Our molecular data also confirm the presence of a divergent mitochondriallineage in the Tsingy de Bemaraha, which might be assigned to either B. bonsi or B. decaryi, and point to the need of more research on this population.